Quantitative echocardiographic measures in the assessment of single ventricle function post‐Fontan: Incorporation into routine clinical practice. Issue 1 (16th November 2016) - Rios, Rodrigo; Ginde, Salil; Saudek, David; Loomba, Rohit S.; Stelter, Jessica; Frommelt, Peter
Abstract : Background: Quantitative echocardiographic measurements of single ventricular (SV) function have not been incorporated into routine clinical practice. Methods: A clinical protocol, which included quantitative measurements of SV deformation (global circumferential and longitudinal strain and strain rate), standard deviation of time to peak systolic strain, myocardial performance index (MPI), dP/dT from an atrioventricular valve regurgitant jet, and superior mesenteric artery resistance index, was instituted for all patients with a history of Fontan procedure undergoing echocardiography. All measures were performed real time during clinically indicated studies and were included in clinical reports. Results: A total of 100 consecutive patients (mean age = 11.95±6.8 years, range 17 months–31.3 years) completed the protocol between September 1, 2014 to April 29, 2015. Deformation measures were completed in 100% of the studies, MPI in 93%, dP/dT in 55%, and superior mesenteric artery Doppler in 82%. The studies were reviewed to assess for efficiency in completing the protocol. The average time for image acquisition was 27.4±8.8 (range 10–62 minutes). The average time to perform deformation measures was 10.8±5.5 minutes (range 5‐35 minutes) and time from beginning of imaging to report completion was 53.4±13.7 minutes (range 27–107 minutes). There was excellent inter‐observer reliability when deformation indices were blindly repeated. Patients with a single left ventricle had significantly higher circumferential strain and strain rate, longitudinal strain and strain rate, and dP/dT compared to a single right ventricle. There were no differences in quantitative indices of ventricular function between patients <10 vs. >10 years post‐Fontan. Conclusion: Advanced quantitative assessment of SV function post‐Fontan can be consistently and efficiently performed real time during clinically indicated echocardiograms with excellent reliability.